The sum of two numbers is 60. The greater number is 6 more than the smaller number. Which equation can be used to solve for the smaller number? a. x + (x + 6) = 60

b. x − (x + 6) = 60

c. x(x + 6) = 60

d. x(x− 6) = 60

Skip to content# The sum of two numbers is 60. The greater number is 6 more than the smaller number. Which equation can

##
This Post Has 8 Comments

### Leave a Reply

The sum of two numbers is 60. The greater number is 6 more than the smaller number. Which equation can be used to solve for the smaller number? a. x + (x + 6) = 60

b. x − (x + 6) = 60

c. x(x + 6) = 60

d. x(x− 6) = 60

Let's assume x be the smaller number.

Given that, The greater number is 6 more than the smaller number.

So, greater number= x+6.

It's also given that, The sum of two numbers is 60. Which means sum of x and x+6 must be equal to 60. Therefore,

x + (x + 6) = 60

A is the answer for that

The correct answer is A

x+(x+6)=60

Since the greater number is six more than the smaller number, the variable value will be of the smaller number. And since the bigger number is six more than the smaller number, it needs to be in parantheses as x plus six. But, since the value of both the numbers is sixty, the equation will finally become x+(x+6)=60

The right answer is x+(x+6)=60

Step-by-step explanation:

I took the test and got it right

The answer to your problem is X+(X+6)=60

x+(x+6)=60

Step by Step Explanation:

Since the greater number is six more than the smaller number, the variable value will be of the smaller number. And since the bigger number is six more than the smaller number, it needs to be in parantheses as x plus six. But, since the value of both the numbers is sixty, the equation will finally become x+(x+6)=60

33 and 27.

Step-by-step explanation:

Since you asked for 6 more for the greater number, it would be 33 and 27 which would still equal 60.

Brainiest would be great! 😀